The decision sampling framework: a methodological approach to investigate evidence use in policy and programmatic innovation - Mackie, Thomas I. (Implement Sci, 2021)
BACKGROUND: Calls have been made for greater application of the decision sciences to investigate and improve use of research evidence in mental health policy and practice. This article proposes a novel method, “decision sampling,” to improve the study of decision-making and research evidence use in policy and programmatic innovation. An illustrative case study applies the decision sampling framework to investigate the decisions made by mid-level administrators when developing system-wide interventions to identify and treat the trauma of children entering foster care. METHODS: Decision sampling grounds qualitative inquiry in decision analysis to elicit information about the decision-making process. Our case study engaged mid-level managers in public sector agencies (n = 32) from 12 states, anchoring responses on a recent index decision regarding universal trauma screening for children entering foster care. Qualitative semi-structured interviews inquired on questions aligned with key components of decision analysis, systematically collecting information on the index decisions, choices considered, information synthesized, expertise accessed, and ultimately the values expressed when selecting among available alternatives. RESULTS: Findings resulted in identification of a case-specific decision set, gaps in available evidence across the decision set, and an understanding of the values that guided decision-making. Specifically, respondents described 14 inter-related decision points summarized in five domains for adoption of universal trauma screening protocols, including (1) reach of the screening protocol, (2) content of the screening tool, (3) threshold for referral, (4) resources for screening startup and sustainment, and (5) system capacity to respond to identified needs. Respondents engaged a continuum of information that ranged from anecdote to research evidence, synthesizing multiple types of knowledge with their expertise. Policy, clinical, and delivery system experts were consulted to help address gaps in available information, prioritize specific information, and assess “fit to context.” The role of values was revealed as participants evaluated potential trade-offs and selected among policy alternatives. CONCLUSIONS: The decision sampling framework is a novel methodological approach to investigate the decision-making process and ultimately aims to inform the development of future dissemination and implementation strategies by identifying the evidence gaps and values expressed by the decision-makers, themselves. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13012-021-01084-5.